Co-regulation of Sox9 and TGFβ1 transcription factors in mesenchymal stem cells regenerated the intervertebral disc degeneration - Khalid, Shumaila; Ekram, Sobia; Ramzan, Faiza; Salim, Asmat; Khan, Irfan (Frontiers in Medicine, 2023)
Intervertebral disc (IVD) shows aging and degenerative changes earlier than any other body connective tissue. Its repair and regeneration provide a considerable challenge in regenerative medicine due to its high degree of infrastructure and mechanical complexity. Mesenchymal stem cells, due to their tissue resurfacing potential, represent many explanatory pathways to regenerate a tissue breakdown. This study was undertaken to evaluate the co-regulation of Sox9 and TGFβ1 in differentiating human umbilical cord mesenchymal stem cells (hUC-MSC) into chondrocytes. The combinatorial impact of Sox9 and TGFβ1 on hUC-MSCs was examined in vitro by gene expression and immunocytochemical staining. In in vivo, an animal model of IVD degeneration was established under a fluoroscopic guided system needle puncture of the caudal disc. Normal and transfected MSCs were transplanted. Oxidative stress, pain, and inflammatory markers were evaluated by qPCR. Disc height index (DHI), water content, and gag content were analyzed. Histological examinations were performed to evaluate the degree of regeneration. Our finding was such that hUC-MSC transfected with Sox9+TGFβ1 showed a noticeable morphological appearance of a chondrocyte, and highly expressed chondrogenic markers (aggrecan, Sox9, TGFβ1, TGFβ2, and type II collagens) temporally after transfection. Histological observation demonstrated that cartilage regeneration, extracellular matrix synthesis, and collagen remodeling were significant upon staining with H & E, Alcian blue, and Masson’s trichrome stain on day 14. Additionally, oxidative stress, pain, and inflammatory markers were positively downregulated in the animals transplanted with Sox9 and TGFβ1 transfected MSCs. In conclusion, these findings indicate that the combinatorial effect of Sox9 and TGFβ1 substantially accelerates the chondrogenesis in hUC-MSCs. Cartilage regeneration and matrix synthesis were significantly enhanced. Therefore, a synergistic effect of Sox9 and TGFβ1 could be an immense therapeutic combination in the tissue engineering of cartilaginous joint bio-prostheses and a novel candidate for cartilage stabilization.